Kualifikasi Tindak Pidana Pornografi (Studi Kasus Video Porno Artis Ga) - Yodhi P S Huwae; Elsa Rina Maya Toule; Jacob Hattu (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The case that ensnared the artist with the initials GA due to the circulation of this shocking 19-second video began to spread at the end of November 2020. Polda Metro Jaya has named the artist Gisella Anastasia and a man with the initials MYD as suspects in a porn video case that went viral on social media. Gisel and MYD were accused of violating Law No. 44 of 2008 on Pornography, which carries a maximum penalty of 12 years in prison. Sister GA and brother MYD were named suspects, suspected of under Article 4 paragraph 1 Juncto Article 29 and or Article 8 of Law Number 44 concerning Pornography.Purposes of the Research: To Know and Analyze the Application of Article Elements in Law Number 44 of 2008 concerning Pornography and the qualification of GA's Acts as Pornographic Acts.Methods of the Research: The method used is normative legal research. The research approach is a statutory approach and a conceptual approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods.Results of the Research: The results showed that GA's actions were against the law, therefore GA's actions met the criminal element and could be applied to Article 4 Paragraph (1) in conjunction with Article 8 of Law Number 48 of 2008 concerning Pornography. And GA's actions can be qualified as pornographic criminal acts because what GA did was negligence or negligence (lack of care), or lack of attention, and that as stated by GA together with MYD the facts have been obtained. Considering, that based on these facts, it can be seen that GA admits that she is the female actor in an adult video video that went viral on social media some time ago. During the examination while still being a witness, Gisel is also said to have admitted that the video was recorded in 2017, at a hotel in Medan, North Sumatra. The determination of the suspect against Gisel and MYD was after the police conducted two examinations as witnesses and held the case. and that taking into account these circumstances, according to the author, due to his negligence or negligence, it has been fulfilled and proven, therefore the negligence or omission by GA can be held legally responsible.